UNDERSTANDING THE DYNAMICS IN DEVELOPMENT PHILOSOPHY FOUNDATION GEOGRAPHY - Ida Bagus Made Astawa (Jurnal Ilmiah Ilmu Sosial, 2016)
The development of the geography of the early to enter the melinium century has shifted significantly. In terms of approach, the geography has shifted from empirical science-analitycal to historical hermeneutic and critical. However, the shift from one approach to another an approach is not exclusive but rather the development of "area of concern", so that geography no longer rely solely on quantitative methods and modeling, but also on qualitative methods. In terms of the flow of thoughts, post modernism also influenced included eksata field studies on geography, although it is recognized that the paradigm of positivism still dominating. Keywords:        shifted, empirical-analitycal, historical hermeneutic, critical, positivism paradigm, exclusive